Abundance, diversity and diffusion of antibiotic resistance genes in cat feces and dog feces. (1st January 2022) - Yang, Yiwen; Hu, Xinwen; Li, Wenjie; Li, Linfei; Liao, Xindi; Xing, Sicheng
Abstract: The ARG profiles in pet feces, such as cat and dog feces, and their potential threat to environmental safety are still unclear. In this study, ARGs in 45 cat and 28 dog fecal samples were detected, and a diffusion experiment was performed to assess the risk of ARGs diffusion into the air. The results showed that the abundances of ARGs in cat feces and dog feces were high, and the abundance in dog feces (0.89 ± 0.17 copies/bacterial cell) was significantly higher than that in cat feces (0.46 ± 0.09 copies/bacterial cell) ( P < 0.05). The bacterial community, especially Firmicutes and Desulfobacterota in cat feces, and Proteobacteria in dog feces, was the main factor affecting the variation in the ARG profiles, contributing to 31.6% and 32.4% of the variation in cat feces and dog feces, respectively. Physicochemical factors (especially NH4 + -N) and age also indirectly affected the variation in the ARG profiles by affecting the bacterial community. In addition, the ARGs in cat feces and dog feces diffused into the air, but there was no evidence that this diffusion posed a threat to environmental safety and human health. These results can provide reference data for healthy animal breeding and the prevention and control of ARG pollution. Graphical abstract: Image 1 Highlights: There was a high abundance of ARGs in cat and dog feces. ARGs in cat feces and dog feces can diffuse into the air. Bacterial community was the main influencing factor in ARG profile. Physicochemical factors and age indirectly affected the ARG profile.